Implementasi Metode Sinkronisasi Waktu Reference Broadcast Synchronization Menggunakan Media Komunikasi Bluetooth Low Energy - Irwan Primadana Mulya; Agung Setia Budi; Rakhmadhany Primananda (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2021)
Time Synchronization is a method used to synchronize a node on the network. The purpose of Time Synchronization is to equalize the nodes on the network and after the Time Synchronization method is implemented, other supporting methods can be implemented as well. There are various synchronization methods that have been circulating and have been implemented, in this study using the Reference Broadcast Synchronization method in this method using a beacon as a marker for synchronizing the time for the communication media used is Bluetooth Low Energy, the system design in this study uses 3 1 node will serve as BLE Server and 2 nodes will be used as BLE clients. The function of the BLE Server is a trigger that will send a beacon to each BLE Client, the BLE Client will receive the beacon and synchronize the RBS time. The hardware used in this research is the ESP32 microcontroller as the main processing, the DS3231 RTC Module as a timer for each BLE client. The test parameters carried out are the calculation of the accuracy of synchronization of computation time and time when synchronizing time, testing the calculation of the accuracy of the finished system getting a value of 16.3ms, which means synchronization of RBS time on BLE communication media produces a fairly accurate value, while testing computational calculations from the finished system produces a value of 133.1ms which means synchronization of RBS time on BLE communication media produces fast time.